2020
DOI: 10.1038/s41598-020-64298-5
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Twist1-PDGFB signaling mediates hypoxia-induced proliferation and migration of αSMA-positive cells

Abstract: Remodeling of distal pulmonary arterioles (pAs) associated with marked accumulation of pulmonary artery smooth muscle cells (pASMcs) represents one of the major pathologic features of pulmonary hypertension (PH). We have reported that the transcription factor Twist1 mediates hypoxia-induced PH. However, the mechanism by which endothelial Twist1 stimulates SMC accumulation to distal PAs in PH remains unclear. Here, we have demonstrated that Twist1 overexpression increases the expression of platelet-derived grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 65 publications
(66 reference statements)
0
39
0
Order By: Relevance
“…We found that upregulation of Twist1 mediates age-dependent decline in angiogenesis through PGC1α and VEGFR2 expression. Twist1 controls multiple angiogenic pathways (e.g., angiopoietins (Angs)-Tie2 [ 18 , 25 ], VEGF-VEGFR2 [ 24 ], PDGF [ 28 ]). For example, we have reported that Twist1 controls Tie2 expression by binding to its promoter region, E-box [ 18 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that upregulation of Twist1 mediates age-dependent decline in angiogenesis through PGC1α and VEGFR2 expression. Twist1 controls multiple angiogenic pathways (e.g., angiopoietins (Angs)-Tie2 [ 18 , 25 ], VEGF-VEGFR2 [ 24 ], PDGF [ 28 ]). For example, we have reported that Twist1 controls Tie2 expression by binding to its promoter region, E-box [ 18 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse lung ECs were isolated from C57BL6 mice (2M and 24M old) using anti-CD31 conjugated magnetic beads and cultured as reported [ 27 , 28 , 50 ]. De-identified discarded human adipose tissues were collected from Medical College of Wisconsin (MCW) Tissue Bank.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the new elegant study by Mammoto et al provided strong evidence that EndMT in PAEC and PDGF-mediated excessive PASMC proliferation could be interdependent in PH [ 175 ]. The authors found that TWIST1 overexpression increased PDGF-B protein in human PAEC.…”
Section: Introductionmentioning
confidence: 99%
“…Twist1 implication in PH is also related to its contribution to EndoMT and is upregulated in patients with PAH [ 132 , 184 ]. Lentiviral knockdown of Twist1 using shRNA reduced the hypoxia-induced EndoMT as well as the accumulation of αSMA-positive cells in the fibrin gel implanted on the live mice [ 185 ].…”
Section: Gene‑delivery Approaches and Gene Therapymentioning
confidence: 99%